AI MODELS FOR ADAPTIVE LEARNING AND CAREER UPSKILLING IN THE DIGITAL ECONOMY - Mariia Gogoleva (Modern American Journals, 2025)
In the digital economy, characterized by rapid technological change and high demand for new skills, artificial intelligence (AI) is becoming a key tool for adaptive learning and career upskilling . Adaptive AI-based systems enable personalization of educational pathways, adjustment of the complexity and content of materials, prediction of student success, and identification of skill gaps. This article examines modern AI models and frameworks , analyzing practical applications, implementation challenges, ethical aspects, and prospects for the development of adaptive learning and career upskilling in the digital economy.
Keywords: Artificial intelligence (AI), adaptive learning, career upskilling, digital economy, personalized learning, professional mobility, skills of the future, AI models.